Risk Factors of Contrast-Induced Nephropa thy in Patients Undergoing Coronary Intervention Procedures - Ferdiyanti Sari; Taufik Sanjya (Sriwijaya Journal of Internal Medicine, 2023)
Introduction: C oronary intervention (coronary angiography and percutaneous coronary intervention) is a medical procedure that uses significant amounts of contrast, which can lead to an increased incidence of contrast-induced nephropathy (CIN). This study aimed to determine the risk factors for contrast-induced nephrop athy in patients undergoing coronary intervention procedures at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: This study is a cross-sectional analytic observational study. A total of 100 research subjects participated in this study. Univariate analysis of the frequency distribution was performed on the variable test. Bivariate analysis was performed to determine the risk factors associated with CIN in patients undergoing coronary intervention procedures, p<0.05. Results: The results of the study showed that contrast volume ≥ 100 ml was associated with the incidence of CIN, p<0.05. In addition, serum creatinine level > 1.5 mg/dL was associated with the incidence of CIN, p<0.05. Conclusion: Contrast volume ≥ 100 ml and serum creatinine level > 1.5 mg/dl increase the risk of contrast-induced nephropathy in patients undergoing coronary intervention procedures at Dr. M. Djamil General Hospital, Padang, Indonesia.